Interaction Between Aminoglycoside Uptake and Ribosomal Resistance Mutations - Ahmad, M. H. (1980)
Mutants resistant to the 2-deoxystreptamine aminoglycosides hygromycin B and gentamicin were analyzed biochemically and genetically. In hygromycin B-resistant strains, ribosomal alterations were not detectable by electrophoretic or genetic experiments. Rather, as was demonstrated for one strain in detail, resistance to this drug seems to be the consequence of several mutations, each impairing drug accumulation, namely of a deletion of a gene close to the proC marker which potentiates the effect of a second mutation in the unc gene cluster. Three mutants resistant to gentamicin which were previously demonstrated to harbor an altered ribosomal protein, L6, were shown in addition to contain unc. Both the unc and the ribosomal mutation greatly impair the drug accumulation ability of the mutants. Further evidence for the direct effect of ribosomal mutations on the uptake of aminoglycosides was obtained with strains that possess ribosomes with increased affinity for dihydrostreptomycin. Dihydrostreptomycin transport by these cells is greatly stimulated; thus, the hypersensitivity of these mutants is caused by increased binding affinity for dihydrostreptomycin and its secondary effect on the uptake process. Experiments were also performed on the biochemical basis of the third phase of aminoglycoside transport (acceleration phase). The condition for its onset is that ribosomes are active in protein synthesis irrespective of whether the proteins synthesized are functional. This, and the failure to observe the synthesis of new proteins upon the addition of aminoglycosides, do not support the view of autoinduction of a cognate or related transport system.